STUDENT STRATEGIES IN CHANGING THE NEGATIVE STIGMA OF SOCIETY AGAINST LECTURES - Nainggolan, Zulpirandi; hidayad, Riyad; Farruq Siregar, Zidan Azbial; Fikri Lubis, Muhammad Fauzul; Rangga Pramana, Muhammad (Proceeding International Seminar of Islamic Studies, 2023)
The purpose of this study is to examine the causes of the emergence of negative stigma in society towards lectures and the strategies and efforts of students in dealing with or changing this paradigm. Various negative stigmas have developed in society towards lectures both in the form of labeling, stereotypes, loss of status and discrimination against people related to lectures. This study aims to analyze more deeply the description of negative stigma and community behavior towards lectures. the general understanding of society that considers college as an absolute requirement for someone to be successful, where such thinking appears is influenced by the environment, increased unemployment and lack of public knowledge about college. The impact of negative stigma on college is causing exclusion of students in society, losing the confidence of someone who wants to continue their education to college and causing discomfort.